A small book of essays on peacemaking criminology - Gesualdi, Louis J. (Hamilton Books, 2024)
"Peacemaking criminology is a humane, nonviolent, and scientific approach in its treatment of crime and the offender. This is a collection of twelve essays that provides readers with an understanding of peacemaking criminology"-- Provided by publisher